Adolescents' Subjective Social Status Predicts Day‐to‐Day Mental Health and Future Substance Use. (2nd April 2019) - Russell, Michael A.; Odgers, Candice L.
Abstract : Adolescents' subjective social status (SSS) is associated with mental and behavioral health outcomes, independent of socioeconomic status (SES). Many previous findings, however, come from cross‐sectional studies. We report results from a longitudinal study with 151 adolescents identified as at risk for early substance use and behavioral problems sampled from low‐SES neighborhoods. We examined whether adolescent's SSS predicted mental health (depression, anxiety, and inattention/impulsivity) measured over 30 days via ecological momentary assessment and risk for substance use at an 18‐month follow‐up. Results showed that with each perceived step "up" the SSS ladder, adolescents experienced fewer mental health symptoms in daily life and lower future substance use risk after adjusting for objective SES and previous psychopathology. Implications of these findings are discussed.